Dynamic negotiation of cloud computing services in market-oriented environments. (1st January 2013) - O'Sullivan, Timothy; Wood, Bob
An aspiring vision of cloud computing is that it will facilitate the realisation of computing as a fifth utility. Previous research has shown that inadequate support for dynamic negotiation of SLAs is a major obstacle preventing the continued growth and ubiquity of cloud computing frameworks. This paper proposes adoption of an agent-based communication protocol to coordinate a dynamic negotiation process between trading parties within a cloud computing market-oriented environment. The motivation of this research proposal is that adoption of such a technique would have profound implications for the pay-for-use model encapsulated within cloud computing service provision. The paper additionally proposes the realisation of agent-based virtual communities of practice amongst consumers, enabling them to become better informed regarding the service quality of cloud computing providers. The paper appraises the benefits and repercussions of the proposed strategy for both service providers and end users through the construction of a simulation test bed.